Wind Design Loads on Large Billboard Based on Iraqi and ASCE7Standards - Ali, Hasan Hussein; Dawood, Abbas O.; Jaafer, Abdulkhaliq A (International Journal of Psychosocial Rehabilitation, 2020)
In Iraq billboards structures are installed without engineering design therefore, billboards and signs are commonly failed during strong winds, thus engineering design of these structures is necessary from cost and functionality points of view especially for large billboard. This study presented a detailed procedure to determine the design wind loadings on large billboard in Iraq according to two codes, i.e., ASCE7-05 and Iraqi Code IQS301. For each code all factors are presented to correspond the Iraqi topography and environment conditions. The basic wind speed for design purposes is specified according to Iraqi standards IQS301. A numerical comparison between codes is presented based on the different wind loadings namely,Maximum horizontal wind pressure, Maximum total horizontal force, Maximum bending moment, Maximum torsion, the different in wind loadings between codes is presented. It found that ASCE7-05 code more accurate and yields higher wind loads than Iraqi code. It's found that Iraqi code IQS301 yields wind loads less than ASCE7-05 with percent of 78.5%. Also,it's found that Iraqi Code IQS301 in the present edition is not suitable for determine the design wind loads on billboard structures and other flexible structures or structures sensitive to the dynamic wind effects.